DINAMIKA KEBIJAKAN MONETER DALAM SISTEM KEUANGAN ISLAM: TANTANGAN DAN INOVASI DI ERA DIGITAL - Harahap, Radia Havni Sari; Syahputra, Selamat; Febriyano, Fikri; Hasibuan, Reni Ria Armayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study analyzes the dynamics of monetary policy in the Islamic financial system as well as the challenges and innovations that have emerged in the digital era. Using qualitative methods through literature review, this study examines Sharia monetary instruments such as SBIS, SukBI, and the Sharia interbank money market, and assesses their effectiveness in maintaining economic stability. The results of the study show that the combination of Islamic monetary instruments and digital innovation has the potential to strengthen the Islamic financial system in a more inclusive and responsive manner, provided that there is regulatory strengthening, harmonization of Islamic standards, and collaboration between regulators, financial institutions, and technology providers. Keywords: Sharia Monetary Policy, Islamic Financial System, Sharia Fintech